SYSTEM OF PROTECTED VOICE CONTROL AN UNMANNED AERIAL VEHICLE - Александр Юрьевич Лавриненко; Юрий Анатольевич Кочергин; Георгий Филимонович Конахович (Авіаційно-космічна техніка та технологія, 2018)
The article proposes and investigates the system of protected voice radio control by the functions of an unmanned aerial vehicle, which is based on the first developed method of secure transmission of voice commands of radio control and the idea of voice authentication of legal subjects of management, where only the voice radio channel is used to transmit control information, thereby allowing the system to be implemented in existing voice radio systems, where on the betraying side is the subject of control, and as a receiver an unmanned aerial vehicle that performs the spoken voice commands. The proposed idea makes it possible to significantly complicate the struggle of malefactors with this kind of systems, since the frequencies at which the voice mobile radio is operating are in common use, and means fighting with this kind of systems will result in the failure of public voice mobile communications. The system of protected voice control of an unmanned aerial vehicle makes it possible to ensure sufficient confidentiality of the transmitted voice commands from the interception of information with the purpose of illegally capturing or destroying an unmanned aerial vehicle throughout the flight. For the first time, the method of voice authentication of legal subjects of management based on the idea of successive substitution of the authentication parameters of the control subject for each subsequent voice command on the authentication parameters from the database, the sequence of which was performed before the flight in a pseudorandom manner and synchronized. The expediency of using the presented system of protected voice radio control functions of an unmanned aerial vehicle is substantiated and experimentally proved. The results of automatic recognition of voice control commands are evaluated using a classifier constructed using the minimum distance criterion, where the decision on the positive identification of voice commands is made by the criterion of a minimum variance in a given threshold of acceptable recognition. The obtained results of experimental research allow to draw a conclusion about the expediency of further practical application of the presented system of protected voice radio control by the functions of an unmanned aerial vehicle